Encyclopedia of human geography - Kobayashi, Audrey Lynn, 1951- (Elsevier, 2020)
International Encyclopedia of Human Geography, Second edition embraces diversity by design and captures the ways in which humans share places and view differences based on gender, race, nationality, location and other factors - in other words, the things that make people and places different."